2010
DOI: 10.5713/ajas.2010.90298
|View full text |Cite
|
Sign up to set email alerts
|

Subfertility in Males: An Important Cause of Bull Disposal in Bovines

Abstract: The study had two objectives, namely, to estimate the andrological disorders leading to disposal of Karan Fries (KF), Sahiwal cattle and Murrah buffalo bulls and to study the effect of various factors (species/breeds, season of birth and period of birth) on male reproductive parameters. Records on occurrence of subfertility problems and disposal pattern of bulls maintained at the National Dairy Research Institute herd were collected for 15 years (1991 to 2005). Percentage of bulls producing freezable semen was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 3 publications
4
58
4
1
Order By: Relevance
“…Among the reserved breeding bulls, disposal due to poor libido was 7.53% which were comparable with the finding of Khate (2005). Lower percentage of culling in crossbreds bulls due to poor libido was also reported by Mathew et al (1982); Mukhopadhyay et al (2010) and Khatun et al (2013). Poor semen freezability (4.45%) in our present study was lower than the finding of Mathew et al (1982); Suryaprakasam and Rao (1993); Sudheer and Xavier (2000) and Mukhopadhyay et al (2010) in CB bulls.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…Among the reserved breeding bulls, disposal due to poor libido was 7.53% which were comparable with the finding of Khate (2005). Lower percentage of culling in crossbreds bulls due to poor libido was also reported by Mathew et al (1982); Mukhopadhyay et al (2010) and Khatun et al (2013). Poor semen freezability (4.45%) in our present study was lower than the finding of Mathew et al (1982); Suryaprakasam and Rao (1993); Sudheer and Xavier (2000) and Mukhopadhyay et al (2010) in CB bulls.…”
Section: Resultscontrasting
confidence: 57%
“…The major reason of culling was poor semen quality (10.27%) in KF bulls. Our present findings were lower than that reported by Rao et al (1995); Sudheer and Xavier (2000); Khate (2005) and Mukhopadhyay et al (2010) in crossbred bulls. Among the reserved breeding bulls, disposal due to poor libido was 7.53% which were comparable with the finding of Khate (2005).…”
Section: Resultscontrasting
confidence: 56%
“…However, the percent production of freezable semen of the crossbred Karan Fries (KF) bulls (58.46%) was inferior to that of the purebred Sahiwal bulls (81.69%) (Mukhopadhyay et al, 2010). Studies have reported that impaired semen production capacity, poor libido, and low freezability are the major reasons for the rejection of the semen of crossbred bulls in the semen collection stations (Sethi et al, 1989;Sahni and Mohan, 1998).…”
Section: Introductionmentioning
confidence: 94%
“…In a breeding farm, extent of variations of semen quality over a long period may depend on existing macro-and micro-climatic conditions, feeding and general management, besides the sexual activity of the animal influenced by surrounding environment during semen collection (Mandal et al 2000). Semen quality is affected by breed (Mukhopadhyay et al 2010); reproductive health status of bulls, technical skills, age (Mandal et al 2010;Ahmad et al 2011), and genetic constitution of bull (Koivisto et al 2009) over a long period may not be consistent as it is not under a single managemental hand.…”
Section: Introductionmentioning
confidence: 99%